The association of adolescent spinal-pain-related absenteeism with early adulthood work absenteeism: A six-year follow-up data from a population-based cohort - Pieter Coenen; Anne Smith; Peter Kent; Mark Harris; Steven J Linton; Glenn Pransky; Darren Beales; Peter O'Sullivan; Leon Straker (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVES: Spinal (ie, back and neck) pain often develops as early as during adolescence and can set a trajectory for later life. However, whether early-life spinal-pain-related behavioral responses of missing school/work are predictive of future work absenteeism is yet unknown. We assessed the association of adolescent spinal-pain-related work or school absenteeism with early adulthood work absenteeism in a prospective population-based cohort. METHODS: Six year follow-up data from the Western Australian Pregnancy Cohort (Raine) study were used (N=476; with a 54% response rate). At age 17, participants reported spinal pain (using the Nordic questionnaire) and adolescent spinal-pain-related work/school absenteeism (with a single item question). Annual total and health-related work absenteeism was assessed with the Health and Work Performance questionnaire distributed in four quarterly text messages during the 23rd year of age. We modelled the association of adolescent spinal-pain-related absenteeism with work absenteeism during early adulthood, using negative binomial regression adjusting for sex, occupation and comorbidities. RESULTS: Participants with adolescent low-back or neck pain with work/school absenteeism reported higher total work absenteeism in early adulthood [148.7, standard deviation (SD) 243.4 hours/year], than those without pain [43.7 (SD 95.2) hours/year); incidence rate ratio 3.4 (95% CI 1.2-9.2)]. Comparable findings were found when considering low-back and neck separately, and when considering health-related absenteeism. CONCLUSIONS: We found a more than three-fold higher risk of work absenteeism in early adulthood among those with adolescent spinal-pain-related absenteeism, compared to those without. These findings suggest that, to keep a sustainable workforce, pain prevention and management should focus on pain-related behaviors as early as in adolescence.